PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. UJB WATER SOLUTIONS DI KABUPATEN GARUT - Pina Pinarti Gistiani; Angga Rovita (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract. This study aims to analyze the influence of leadership style and work discipline on employee performance at PT. UJB Water Solutions. The background of this research is the fluctuation in employee performance shown from 2020-2024 data with average achievement declining from 82.0% (2020) to 71.0% (2024), and high indisciplinary cases with an average of 66.4 cases per year. The research method used is quantitative research with causal associative approach. The research population is all employees of PT. UJB Water Solutions totaling 65 people using saturated sampling technique. Data collection using questionnaires with Likert scale and data analysis using multiple linear regression with SPSS version 27. The results showed that: (1) Leadership style has a positive and significant effect on employee performance with coefficient of determination value of 19.5% and t value 2.966 > t table 1.998; (2) Work discipline has a positive and significant effect on employee performance with coefficient of determination value of 70.0% and t value 11.318 > t table 1.998; (3) Leadership style and work discipline simultaneously have a significant effect on employee performance with coefficient of determination value of 73.8% and F value 87.147 > F table 3.150. This study concludes that work discipline has a more dominant influence than leadership style in improving employee performance at PT. UJB Water Solutions.